Upward refinement operators for conceptual blending in the description logic - Confalonieri, Roberto; Eppe, Manfred; Schorlemmer, Marco; Kutz, Oliver; Peñaloza, Rafael; Plaza, Enric (Annals of mathematics and artificial intelligence, 2018)
Conceptual blending is a mental process that serves a variety of cognitive purposes, including human creativity. In this line of thinking, human creativity is modeled as a process that takes different mental spaces as input and combines them into a new mental space, called a blend . According to this form of combinational creativity , a blend is constructed by taking the commonalities among the input mental spaces into account, to form a so-called generic space , and by projecting the non-common structure of the input spaces in a selective way to the novel blended space. Since input spaces for interesting blends are often initially incompatible, a generalisation step is needed before they can be blended. In this paper, we apply this idea to blend input spaces specified in the description logic 𝓔 𝓛 + + and propose an upward refinement operator for generalising 𝓔 𝓛 + + concepts. We show how the generalisation operator is translated to Answer Set Programming (ASP) in order to implement a search process that finds possible generalisations of input concepts. The generalisations obtained by the ASP process are used in a conceptual blending algorithm that generates and evaluates possible combinations of blends. We exemplify our approach in the domain of computer icons.